2013
DOI: 10.4161/auto.22801
|View full text |Cite
|
Sign up to set email alerts
|

Integrated regulation of autophagy and apoptosis by EEF2K controls cellular fate and modulates the efficacy of curcumin and velcade against tumor cells

Abstract: Endoplasmic reticulum (ER) stress induces both autophagy and apoptosis yet the molecular mechanisms and pathways underlying the regulation of these two cellular processes in cells undergoing ER stress remain less clear. We report here that eukaryotic elongation factor-2 kinase (EEF2K) is a critical controller of the ER stress-induced autophagy and apoptosis in tumor cells. DDIT4, a stress-induced protein, was required for transducing the signal for activation of EEF2K under ER stress. We further showed that ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…The mTOR signaling pathway regulates the activity of the ULK1 protein activated complex, suppressing autophagy (33). EEF2K is a calcium/calmodulin-dependent enzyme and increases in EEF2K expression can trigger autophagy (13,34,35). Studies have found that the mTOR signaling pathway promotes EEF2K degradation through phosphorylating the Ser78/Ser366 site of EEF2K, resulting in decreased autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mTOR signaling pathway regulates the activity of the ULK1 protein activated complex, suppressing autophagy (33). EEF2K is a calcium/calmodulin-dependent enzyme and increases in EEF2K expression can trigger autophagy (13,34,35). Studies have found that the mTOR signaling pathway promotes EEF2K degradation through phosphorylating the Ser78/Ser366 site of EEF2K, resulting in decreased autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the mTOR signaling pathway promotes EEF2K degradation through phosphorylating the Ser78/Ser366 site of EEF2K, resulting in decreased autophagy. As an inhibitor of mTOR, REDD1 can stabilize EEF2K expression through the mTOR-EEF2K pathway to promote autophagy (13). Therefore, a REDD1-EEF2Kautophagy regulation axis exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, autophagy can play a protective or destructive role in disease states, and thus for therapeutic purposes it would be valuable to identify and develop pharmacologic agents that can induce or inhibit this cellular process. A variety of potentially "druggable" targets affecting autophagy have been identified such as eEF2K, which acts as a positive regulator of autophagy under various stresses, as reported by our laboratory (Wu et al, 2009;Cheng et al, 2011aCheng et al, , 2013.…”
Section: A Mechanism Of Action Of Autophagy Modulatorsmentioning
confidence: 83%
“…Eukaryotic elongation factor 2 kinase (eEF2K) plays roles in protecting cells against stressful conditions, including nutrient starvation [1][2][3] and also anti-cancer agents [4,5], as well as in neurological processes [6] such as dendritic stability [7], long-term potentiation [8] and learning/memory [9]. eEF2K is a member of the small family of so-called α-kinases, rather than of the main protein kinase superfamily [10,11].…”
Section: Introductionmentioning
confidence: 99%